The social aspects in the identification of children's mental health problems in two health services in Paris, France - Eunice Nakamura; Maëlle Planche; Alain Ehrenberg (Faculdade de Medicina de Botucatu (Unesp), 2017)
Children's mental health problems were analyzed from a sociological approach addressing two questions: what are the main children's behaviors identified and considered to be mental health problems, and what are the consequences of this classification for the debate on children's problems in contemporary societies. This quantitative and qualitative study analyzed 275 patients' records from two child mental health services (CMHS) in the northeast area of Paris, France. The majority of children were boys from six to 11 years old; requests were presented mainly by schools and parents; the main problems were behavioural problems, cognitive difficulties and relational problems (boys), and affective or emotional problems (girls). There is an interdependence of a great number of actors who worry about children's behavior and a system of expectations seems to be collectively woven by them as social classifications.